(untitled) (Ameghiniana, 2013)
Additional microplankton from the well SEAB x - 1 (Santiago del Estero - Arbol Blanco) at 2.650 m depth in Copo Formation is studied. The described forms confirm the Ludlovian age formerly assigned to the lower part of the Formation, showing that they are closely related with the Upper Silurian forms from the San Pedro formation in Spain. Priscogalea Deunff is discussed here, with its variations in species and genera. A new genus, Downiea n. gen., is erected; its differences with Deunffia Downie and Demasia Downie are discussed.